Carbon footprint of transport and mobility : the case of a higher education institution - Alvarez Franco, Diego (2021)
The study of climate change, its consequences and implementing strategies to combat climate change are one of the current challenges of this century. Transport and mobility have been recognized as important contributors to the overall environmental carbon footprint of higher education institutions. Universities, as job and knowledge providers have a great stake to influence the indirect transport and mobility emissions of personnel and students. In this study, carbon footprint evaluation was carried out to calculate the annual travel and mobility emissions produced by personnel and students of the University of Jyväskylä. Through the implementation of consumption-based carbon footprint, this study evaluated the emissions from commuting travels, long-distance leisure travels and unreported business travels. The study collected primary data to discover distances and transport modes to measure the emissions produced per person and to estimate the total transport and mobility carbon footprint of the University. The findings revealed that personnel produced an average of 0.5 t CO2-eq emissions per person per year while students produced an annual average of 0.3 t CO2-eq emissions per person. Personnel produced 67% of the commuting emissions while students produced 85% of the long-distance leisure travel emissions. However, the majority of the emissions were produced by car use. Yet students produced 54% of the emissions while personnel produced 46%. The total estimated emissions production of students was 3,930.6 t CO2-eq per year and personnel produced 1,363 t CO2-eq emissions per year. Hence, the overall annual transport and mobility carbon footprint estimation of the University was 5,2293.7 t CO2-eq. The findings of this study suggest reducing the use of car and switch to a low-carbon transport. The study also recommends to implement soft policies, campaigns and incentives to reduce the use of cars as an important hotspot of the University. However, more research is required to find out the reasons of car use and to mitigate transport emissions in the future.